Pengaruh Variasi Suhu Dan Waktu Inkubasi Terhadap Aktivitas Enzim Selulase Dari Bakteri Serratia marcescens - Kurniawati, Laily; Kusdiyantini, Endang; Wijanarka, W (Bioma : Berkala Ilmiah Biologi, 2021)
Enzymes are biocatalysts in living cells when cells metabolize. All living organisms are produced enzymes, both humans, animals, plants and microorganisms. One of the bacteria that has the potential to produce cellulose (EC 3.2.1.4) enzymes is Serratia marcescens. These bacteria can be isolated from water, soil and digestive tract. This research aims to find out the types of enzymes produced by S. Marcescens, to examine the effect of temperature and incubation time on selected enzyme activity. The type of enzyme test was qualitatively determined by S. marcescens growth on the amylolytic, cellulolytic, pectinolytic and chitinolytic selective medium based on the clear zone. This research was used a Completely Randomized Design (CRD). The first factor was the incubation time (T) which were 4 hours (T4), 8 hours (T8) and 12 hours (T12). The second factor was the treatment of incubation temperature (S) which were 40oC (S1), 50oC (S2) and 60oC (S3). Each treatment was repeated in 3 times. The data were obtained then analyzed using Anova (Î± = 0.05). If it is significantly different, furthermore proceed with the T test (BNT). The results showed that S. marcescens qualitatively produced only clear zones in the cellulolytic medium of 5.1 mm. The ANOVA results showed that incubation temperature (S), the interaction between incubation time (T) and incubation temperature (S) were did not have effect on cellulase activity, whereas incubation time (T) Â gives a significant effect on cellulase activity were obtained at the incubation time for 12 hours (T12) with a value of 0.27 U / mL